Multistimuli-responsive microrobots: A comprehensive review - Shah, Zameer Hussain; Wu, Bingzhi; Das, Sambeeta (Frontiers in Robotics and AI, 2022)
Untethered robots of the size of a few microns have attracted increasing attention for the potential to transform many aspects of manufacturing, medicine, health care, and bioengineering. Previously impenetrable environments have become available for high-resolution in situ and in vivo manipulations as the size of the untethered robots goes down to the microscale. Nevertheless, the independent navigation of several robots at the microscale is challenging as they cannot have onboard transducers, batteries, and control like other multi-agent systems, due to the size limitations. Therefore, various unconventional propulsion mechanisms have been explored to power motion at the nanoscale. Moreover, a variety of combinations of actuation methods has also been extensively studied to tackle different issues. In this survey, we present a thorough review of the recent developments of various dedicated ways to actuate and control multistimuli-enabled microrobots. We have also discussed existing challenges and evolving concepts associated with each technique.